Sitem pendukung keputusan pemilihan SMA Terbaik Menggunakan Metode WASPAS di Kota Kupang - Lakh, Beci Siana; Meo, Meliana (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2025)
Education is a crucial aspect in developing high-quality human resources. Kupang City, the largest city on Timor Island, has 62 senior high schools offering various advantages. However, the wide range of options often makes it difficult for students and parents to choose a school that suits their needs. The selection process, which is often carried out subjectively, can lead to less optimal decisions. This study aims to develop a decision support system to assist in selecting the best senior high school (SMA). The method used in this research is the WASPAS method, which has the advantage of producing optimal decisions by considering both the maximum and minimum values of the criteria simultaneously, making it suitable for decision-making problems involving specific criteria. The expected outcome of this research is to help parents and students in choosing the best senior high school